The Role of Artificial Intelligence (AI) in the Efficiency of Islamic Education Management: Opportunities and Challenges - Pauzi Pauzi; Sudanto Sudanto (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to examine the role of Artificial Intelligence (AI) in improving the efficiency of Islamic education management and to identify the opportunities and challenges that arise when AI is implemented. This study used a literature review method, compiling scientific articles, policy reports, and research findings from the past five years, from 2020 to 2025. The results indicate that AI offers numerous opportunities to improve administrative efficiency, enhance learning that can be tailored to student needs, support data-driven evaluation, and provide faster and more accurate academic services. Furthermore, AI also opens up opportunities to digitize the Islamic curriculum to better align with student needs and current developments. However, this study also identified several challenges. Ethical issues, personal data protection, limited digital infrastructure, educators' limited ability to use technology, and the risk of over-reliance on technology are key obstacles. Furthermore, if AI is implemented without adherence to Islamic values, it could lead to a mismatch between the goals of technology and the vision of Islamic education. Therefore, the use of AI needs to be directed wisely to align with Sharia principles and the goals of Islamic education. Thus, it can be concluded that AI is a crucial tool in accelerating the modernization of Islamic education management to make it more efficient, adaptive, and globally competitive. However, the success of AI implementation depends heavily on clear regulations, human resource readiness, supporting infrastructure, and an ethical framework grounded in Islamic values.